Tenth Five-Year Plan (2002-2007) and Annual Plan (2003-2004) Government of Himachal Pradesh - Planning Commission (Planning Commission, 2002)
Survey of India, the minerals available in Himachal Pradesh include lime stone, byrytes, Himachal Pradesh is blessed with mineral wealth. As per investigation of Geological clays, mica, iron-pyrites, salt, gypsum, slate, antimony and lead.The distribution of these minerals is scattered all over the State and includes lime stone in Bilaspur, Sirmaur and Kangra districts; Salt and Slates in Mandi District; Gypsum in Rajban Bharli Sirmour dist..; Lahaul & Spiti and Sapatu in Solan dist..; Byryte in Sirmour, Iron ore in Mandi and Kangra; and uranium in Kullu and Hamirpur.
Planning Department, Government of Himachal Pradesh